Potato Market Access, Marketing Efficiency And On-Farm Value Addition In Uganda - Kyomugisha, Harriet; Sebatta, Christopher; Mugisha, Johnny (Scientific African, 2018)
Understanding barriers to market access for smallholder farmers and their marketing efficiency when they participate in agricultural value chains is key to unlocking the market potential and overcoming market failures. This study aimed at determining factors limiting farmers’ market access, the break-even point for undertaking postharvest value addition activities by the farmers, and the market efficiency of the Uganda potato market chains in which the smallholder farmers are participating. Our study was based on the hypothesis that market access and efficiency are higher where farmers have contract arrangements with buyers, and where they are directly linked with the buyers at the end of the value chain. The study was carried out in the popular potato growing districts of Kabale and Mbale in Uganda. The survey involved purposive selection of the study areas and random selection of potato farmers and traders. We used an Ordinary Least Square model to determine factors that influence potato smallholder farmers’ market access. We also used break-even analysis to determine the break-even point for potato farmers to take up postharvest value addition activities, and a value addition approach to determine market efficiency. Results indicate that having a contract with buyers, size of land owned, number of forked hoes owned and variety grown positively and significantly influenced farmer market access. We found that adding value to potato on farm earns farmers relatively more income. A farmer would earn 25% higher than when no value addition was done. Market chains where farmers sell to local rural traders were more efficient than selling to other alternatives. We recommend farmer involvement in value addition, collective and/or contractual marketing, and selling directly to the nearest actor in the value chain.
Keywords: Market access; Market chains; Potato; Smallholder; Value addition